(untitled) (Bangladesh Journal of Neuroscience, 2013)
A rare clinical presentation arterial Thoracic outlet syndrome (TOS) is described in a young school-girl. TOS causing distal; disease is a rare cause of artery to- artery embolic stroke. Brain-stem ischemic stroke is a result of compromise to the posterior circulation. This is often due to antegrade embolism from the heart or proximal vessels. Retrograde blood flow has been described in the subclavian artery, thus making the distal subclavian artery a source of possible retrograde embolism to carotid circulation1. Clinical presentation also included left hemiparesis caused by right subclavian artery thrombosis and retrograde embolizatoin of thrombus via common carotid artery to the right middle cerebral artery (MCA) distribution. Bangladesh Journal of Neuroscience 2012; Vol. 28 (1): 63-66